Measuring Index Investment in Commodity Futures Markets - Sanders, Dwight R.; Irwin, Scott H. (The Energy journal (Cambridge, Mass.), 2013)
The "Masters Hypothesis "is the claim that unprecedented buying pressure in recent years from new index investment created a massive bubble in commodity futures prices. Due to data limitations, some recent studies of the market impact of index investment in the WTI crude oil futures market impute index positions. We investigate the accuracy of the algorithm popularized by Masters (2008) to estimate index positions. The estimates generated by the Masters algorithm deviate substantially from the positions reported in the U.S. Commodity Futures Trading Commission's (CFTC) Index Investment Data (HD) report—the agency's best data on index positions. The Masters algorithm over-estimates the gross WTI crude oil position by an average of 142,000 contracts. Importantly, the deviation in the first half of 2008, the period of greatest concern about the market impact of index investment, is directionally wrong. These results suggest empirical tests of market impact based on mapping algorithms in WTI crude oil futures should be viewed with considerable caution.